2012
DOI: 10.1029/2011jc007355
|View full text |Cite
|
Sign up to set email alerts
|

Iron, nutrients, and humic‐type fluorescent dissolved organic matter in the northern Bering Sea shelf, Bering Strait, and Chukchi Sea

Abstract: The concentrations of dissolved Fe ([DFe]), total dissolvable Fe, humic‐type fluorescence intensity (humic F intensity) as humic‐type fluorescent dissolved organic matter (humic‐type FDOM), and nutrients were determined vertically in the northern Bering Sea shelf (Yukon River estuary region and St. Lawrence Island polynya region), the eastern Chukchi Sea shelf (Chukchi shelf polynya region), and the central Bering Strait during 30 July to 12 August 2007 and 30 June to 12 July 2008. In early July 2008, with a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 106 publications
2
45
0
Order By: Relevance
“…Here, N* is the deviation of the nitrogen concentration from the stoichiometric relationship between nitrogenous nutrients and phosphate, and large negative values indicate the occurrence of significant denitrification within the shelf sediments1920. In contrast, the high Fe is probably attributable to high Fe inputs from rivers21 and melting ice into nutrient-depleted surface waters. Denitrification, in which nitrate instead of oxygen is consumed during the bacterial decomposition of organic matter in low-oxygen waters in sediment pores, causes N* to decrease independently of the phosphate level.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, N* is the deviation of the nitrogen concentration from the stoichiometric relationship between nitrogenous nutrients and phosphate, and large negative values indicate the occurrence of significant denitrification within the shelf sediments1920. In contrast, the high Fe is probably attributable to high Fe inputs from rivers21 and melting ice into nutrient-depleted surface waters. Denitrification, in which nitrate instead of oxygen is consumed during the bacterial decomposition of organic matter in low-oxygen waters in sediment pores, causes N* to decrease independently of the phosphate level.…”
Section: Resultsmentioning
confidence: 99%
“…Above the continental shelves of the Bering and Chukchi seas, cold, dense deep and bottom waters are characterized by high levels of nutrients, humic F-intensity, and Fe, and by denitrification/anammox, because of the transport of chemical species across the sediment–water interface during early diagenesis262123 (Fig. 7g).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Arctic region, in situ studies have reported high dissolved iron concentrations in the Laptev Sea, the Fram Strait, the Bering Strait, and the Chukchi Sea: values are > 10 nM ), 5.7-23.1 nM (Tovar-Sanchez et al, 2010, 5-10 nM (Nishimura et al, 2012), and 2.1-16.3 nM (Nishimura et al, 2012), respectively. Lower concentrations are observed in other Arctic regions.…”
Section: Iron Distribution In Sea Ice and Watermentioning
confidence: 99%